It's Not About Being Generous: Platform Leaders and Patent Shelters. Issue 2 (3rd March 2016) - Bagheri, Seyed Kamran; Minin, Alberto Di; Paraboschi, Andrea; Piccaluga, Andrea
OVERVIEW: On August 12, 2011, Google filed a request with the US Patent and Trademark Office (USPTO) for the reexamination of two patents used by Lodsys to file lawsuits against several Android coders. The first public move of the Internet giant to defend Android application developers from patent lawsuits, this filing is just one of a growing number of initiatives undertaken by platform leaders to protect independent complementors against patent litigation threats. We examine the emerging evidence on platform leaders' initiatives to provide patent shelter for their partners, which we argue helps maintain and reinforce the platform ecosystem. Platform leaders' defensive responses are directed at two different levels: (1) providing umbrella protection to the whole platform, and (2) offering defensive intervention in specific cases. We propose a conceptual framework that categorizes platform leaders' case-specific reactions under three different scenarios and look at the evolution of patent sheltering over time and the practical implications of its emergence.